Nominal incorporation in parkatêjê: syntatic or lexical process? (2011)
According to the specialized literature, there are two types of nominal incorporation across languages. The first one is a syntactic process in which a nominal nuclear argument juxtaposes to the verb, resulting in a complex verb of restricted meaning. In the other one, similar to lexical composition, two lexical items are put together to form a third one. This paper describes the nominal incorporation in Parkatêjê, which occurs as a lexical process.